Music: A tool in transforming the Social Status of Special needs Children - Tepika Rodsakan (IJCAS (International Journal of Creative and Arts Studies), 2018)
There are some attempts to politically encourage the rights of social status to Special Needs Children by both Thai government and non-government organizations. Practically, the fact indicates that the Special Needs Children’s social status and roles are vaguely partial in terms of whether opportunities or social rights. The researcher has experimented by organizing traditional Thai musical activities to Special Needs Children, the case study of Panyawutikorn School. Pre-test and post-test results and observation evidently have shown that the musical skills are increasingly improved. Similarly, an empirical data presents they took pride proudly when they are being praised in their developing skills by teachers, parents as well as H.R.H. Mahachakri Sirindhron princess, has been at Panyawutikorn school in order to attend Thai musical performance of Special Needs Children, the attention of princess can encourage them to be more engaged in musical performance of Special Needs Children and also people involved. As mentioned above, ‘music’ is utilized as a tool to transforms the social status and give them a chance of playing role as givers. The traditional Thai music ensemble of Special Needs Children is requested to broadly show their abilities in many places such as hospitals, elderly cares, and in other school activities. Truly, music therefore is effectively able to transmit the social status of the Special Needs Children from previously they were defined as always receivers to be currently understood as givers. Furthermore, the study also provided the number of children is stepping up and paying more attentions in musical activities. This is to really consider the attempts to push up Special Needs Children in the same level of citizenship hierarchy.